A 0.6V improved PSRR bandgap reference for power management system in RF energy harvesting applications - Zulkalnain, Mohd Khairi (2021)
The scaling of technology to lower process nodes is a major convenience as it allows for power saving by allowing the circuit to operate at a lower voltage. As per the prediction by International Technology Roadmap for Semiconductors (ITRS), the supply voltage will reduce down to 0.4V by 2024. Although the reduction of supply voltage is favourable in terms of power-saving, especially in powering Internet of Things (IoT) devices, the penalty incurred by this is the degradation of power supply rejection ratio (PSRR) due to reduced output impedance of bandgap reference circuits at lower voltage supply. The proposed work aims to mitigate this problem by employing metal oxide semiconductors (MOS) based proportional to absolute temperature (PTAT) and complementary to absolute temperature (CTAT) generator and regulated cascode techniques to improve the PSRR even at lower voltage supply, eliminating the need for voltage doubler circuits which injects noise in the substrate and degrades circuit performance. This improved PSRR bandgap reference circuit will then be used to power-up circuits that require high PSRR and clean power supply to ensure optimal functionality of IoT circuits, particularly sensitive circuits that degrade in functionality when subjected to noise travelling through power supply such as low power sensors and voltage controlled oscillators (VCOs) in frequency synthesizers. The objectives of this work are to investigate the characteristics and performances of the power management unit for radio frequency energy harvesting (RFEH) applications, design and develop bandgap reference with improved PSRR at low voltage supply, design and develop a low dropout (LDO) regulator to provide a constant voltage reference in RFEH system and validate and analyze the performance of the proposed circuit. This work managed to achieve a reference voltage of 0.405V over a wide temperature of -40 to 125˚C, a PSRR of -41dB, line and load regulation of 1.188mV/V and 2.506mV/mA respectively and load current range from 0 to 800µA. The current consumption of the bandgap is 20.33µA and the whole power management unit (PMU) is 37µA and the temperature coefficient (TC) is 64.41ppm/˚C. The bandgap area is 0.0627mm2 while the whole PMU is 0.142mm2. Overall, the design passes all the post layout validations such as design rule check (DRC) and layout vs schematic (LVS) and functions as expected. The post-layout simulations were analyzed and the results closely agree with the pre-layout simulations. On top of that, this work demonstrates the robustness of the bandgap reference circuit when integrated at the top level with the LDO, start-up and biasing circuits as it is able to operate, with 50% improvement in PSRR over conventional design at a supply voltage of 0.6V, making it suitable to power up sensitive IoT circuits.